BESOINS EDUCATIFS DES JEUNES DESOEUVRES DE LA VILLE DE KISANGANI « CAS DE LA COMMUNE MAKISO » - Eugene Baelongandi Looho (IJRDO- Journal of Educational Research, 2025)
School education therefore appears to be a force on which the development of a country, a region, or a city must rely. It therefore turns out to be unavailable to train the man who will be able to deal with the problems of his environment. Popular education requires that its actors, in collaboration with the masses of young people, be able to identify with much more lucidity the problems which arise in the environment and which handicap its development, thus, the program of this education must be developed with perfect knowledge of the real needs and interests of young people. While receiving this education, young people very often express in a particular way a need for training in various specific areas of life, allowing them to perfect their knowledge to raise their level of social existence (MAEMBO, P.1997, P) . The school must therefore train productive, creative, cultured, conscientious, free and responsible citizens, open to social, cultural and aesthetic, spiritual and republican values. The training of the Congolese man must be total, coherent, balanced and complete. Every human society must ensure realistic conditions for reproductive survival through education. This is considered as a dynamic transformation that occurs through an assimilation and critical absorption of the tradition by which society recognizes itself in what is essential to it.